The Natural Agonist of Estrogen Receptor β Silibinin Plays an Immunosuppressive Role Representing a Potential Therapeutic Tool in Rheumatoid Arthritis - Dupuis, Maria Luisa; Conti, Fabrizio; Maselli, Angela; Pagano, Maria Teresa; Ruggieri, Anna; Anticoli, Simona; Fragale, Alessandra; Gabriele, Lucia; Gagliardi, Maria Cristina; Sanchez, Massimo; Ceccarelli, Fulvia; Alessandri, Cristiano; et al. (Frontiers in Immunology, 2018)
Estrogens, in particular 17β-estradiol (E2), have a strong influence on the immune system and also affect pathological conditions such as autoimmune diseases. The biological effects of E2 are mediated by two intracellular receptors, i.e., estrogen receptor (ER)α and ERβ, which function as ligand-activated nuclear transcription factors producing genomic effects. Immune cells express both ERα and ERβ that play a complex role in modulating inflammation. Phytoestrogens display estrogen-like effects. Among them, silibinin, the major active constituent of silymarin extracted by the milk thistle (Silybum marianum), has been suggested to have an ERβ selective binding. Silibinin is known to have anti-inflammatory, hepatoprotective and anticarcinogenic effects; however, the role of silibinin in modulating human immune responses and its impact on autoimmunity remains unclear. Aim of this study was to dissect the ability of the ERβ natural ligand silibinin to modulate T cell immunity, taking into account possible differences between females and males, and to define its possible role as therapeutic tool in immune-mediated diseases. To this purpose, female and age-matched male healthy subjects and patients with active rheumatoid arthritis (RA) were recruited. We evaluated the ability of silibinin to modulate ERβ expression in T lymphocytes and its effects on T cell functions (i.e., apoptosis, proliferation and cytokine production). We also analyzed whether silibinin was able to modulate the expression of microRNA 155 (miR-155), which strongly contributes to the pathogenesis of RA driving aberrant activation of the immune system. We demonstrated that silibinin upregulated ERβ expression, induced apoptosis, inhibited proliferation and reduced expression of the pro-inflammatory cytokines IL-17 and TNF-α, through ERβ binding, in T lymphocytes from female and male healthy donors. We obtained similar results in T lymphocytes from patients with active RA in term of apoptosis, proliferation and cytokine production. In addition, we found that silibinin acted as an epigenetic modifier, down-modulating the expression of miR-155. In conclusion, our data demonstrated an immunosuppressive role of silibinin, supporting its application in the treatment of autoimmune diseases as drug, but also as dietary nutritional supplement, opening new perspective in the field of autoimmune disease management.